Pengaruh Harga Dan Kepercayaan Merek Terhadap Minat Beli Air Minum Aqua Galon Di Medan Perjuangan - Gulo, Suci Sang Primadona; Manalu, Darma; Simangunsong, Ridhon NB. (Research and Community Service UNIVERSITAS KALBIS, 2024)
The need for clean water is currently increasing, especially the need for drinking water, because the population is increasing. However, through current development innovations, people do not experience difficulties in getting clean drinking water and have passed the laboratory test as drinkable. This study aims to determine the effect of price and brand trust on the public's repurchase interest in Aqua gallon drinking water in Medan Perjuangan District. Research Methods: Shows that Price (X1) has a negative effect and does not have a significant effect on purchasing interest (Y), brand trust (X2) has a positive and significant effect on purchasing interest (Y). While price (X1) and Brand Trust (X2) simultaneously have a significant effect on purchasing interest (Y). Conclusion: The results of this study can be concluded that Price (X1) has a negative effect and does not have a significant effect on purchasing interest (Y), brand trust (X2) has a positive and significant effect on purchasing interest (Y), while price (X1) and brand trust (X2) simultaneously have a significant effect on purchasing interest (Y)